1997
DOI: 10.1085/jgp.110.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Wild-Type and Mutant Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channels to Polyatomic Anions

Abstract: Permeability of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel to polyatomic anions of known dimensions was studied in stably transfected Chinese hamster ovary cells by using the patch clamp technique. Biionic reversal potentials measured with external polyatomic anions gave the permeability ratio (PX/PCl) sequence NO3 − > Cl− > HCO3 − > formate > acetate. The same selectivity sequence but somewhat higher permeability ratios were obtained when anions were tested from the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
204
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(236 citation statements)
references
References 52 publications
(109 reference statements)
29
204
3
Order By: Relevance
“…These fast exchanging proteins share the common function of transporting relatively large hydrophilic molecules, and consequently it is expected that they should possess a large hydrophilic pore. Because CFTR has been shown to be permeant not only to chloride but also to polyatomic anions (45) and to glutathione (46,47), it certainly shares the same properties. Moreover, the modification of the exchange rate upon phosphorylation implies that it induces a large conformational change that modifies the accessibility of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…These fast exchanging proteins share the common function of transporting relatively large hydrophilic molecules, and consequently it is expected that they should possess a large hydrophilic pore. Because CFTR has been shown to be permeant not only to chloride but also to polyatomic anions (45) and to glutathione (46,47), it certainly shares the same properties. Moreover, the modification of the exchange rate upon phosphorylation implies that it induces a large conformational change that modifies the accessibility of CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anion permeation in the CFTR chloride channel shows a weak dependence on the anion's hydration energy (Table 1). 11,13 We observed a nonlinear dependence of the rate constant for anion transport on the concentration of transporter 3 ( Figure S11). This result indicated that anion transport became more efficient when bis-catechol 3 self-associates in the membrane.…”
mentioning
confidence: 93%
“…A similar model to explain HCO 3 -secretion by the pancreatic duct of non-rodent eutherian mammals has been proposed (Park et al, 2010;Steward et al, 2005). CFTR from eutherian mammals also has a relatively low P HCO3 (Gray et al, 1993;Gray et al, 1990;Linsdell et al, 1997;O'Reilly et al, 2000;Poulsen et al, 1994). However, in the pancreatic duct cells it has been suggested that HCO 3 -secretion occurs via CFTR because there is no mechanism on the basolateral membrane to accumulate Cl -, whereas there is a mechanism for HCO 3 -accumulation (Fernández-Salazar et al, 2004).…”
Section: Discussionmentioning
confidence: 89%